The role of participants’ self-selected future smoking goals in adolescent smoking cessation interventions - Thrul, Johannes Erich; Stemmler, Mark; Bühler, Anneke; Goecke, Michaela (Drug and Alcohol Dependence, 2014)
BACKGROUND: There is an implicit assumption that abstinence is the treatment goal of young smokers that deliberately participate in cessation interventions, but this may not always be the case. To gain information on subgroups of adolescent intervention participants, we compare participants who want to achieve smoking abstinence (Abst) with those stating a non-abstinence future smoking goal (NAbst), with regard to baseline characteristics, reasons for participation, quit motivation, retention, goal attainment, and smoking abstinence. METHODS: The sample consisted of 202 adolescent smokers (49.5% female). At baseline, 118 (58.4%) indicated abstinence as future smoking goal and 84 (41.6%) indicated non-abstinence. All participants received a behavioral smoking cessation intervention. Assessments took place before, during, and after treatment, and at 6-month follow-up. Regression analyses were conducted. RESULTS: Abst and NAbst participants reported similar baseline characteristics. Abst participants, however, were more likely to report a previous quit attempt and indicated a higher quit motivation before and during treatment. Abst participants were more likely to participate based on own initiative and NAbst participants because of participating friends. Both groups attended a similar number of intervention sessions and were equally likely to attain their self-selected smoking goal. However, more Abst participants reported a successful quit attempt during treatment and abstinence at post-treatment and follow-up. CONCLUSIONS: NAbst participants may represent a substantial subgroup in smoking cessation interventions for adolescents. Results indicate that future smoking goals can influence treatment outcomes. NAbst participants in treatment may benefit from additional information on the negative health consequences of light smoking.